2003
DOI: 10.1210/en.2002-221054
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Like Activity of Metals in Mcf-7 Breast Cancer Cells

Abstract: The ability of metals to activate estrogen receptor-alpha (ERalpha) was measured in the human breast cancer cell line, MCF-7. Similar to estradiol, treatment of cells with the divalent metals copper, cobalt, nickel, lead, mercury, tin, and chromium or with the metal anion vanadate stimulated cell proliferation; by d 6, there was a 2- to 5-fold increase in cell number. The metals also decreased the concentration of ERalpha protein and mRNA by 40-60% and induced expression of the estrogen-regulated genes progest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
247
0
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(267 citation statements)
references
References 53 publications
8
247
0
12
Order By: Relevance
“…The negative association observed between BMI and blood lead concentration for adult women aged 50-65 might be due in part to the xeno-oestrogenic activity of lead described by Martin et al(2003), but a more general toxic effect of lead (Doumouchtsis et al 2009) might also play a role.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The negative association observed between BMI and blood lead concentration for adult women aged 50-65 might be due in part to the xeno-oestrogenic activity of lead described by Martin et al(2003), but a more general toxic effect of lead (Doumouchtsis et al 2009) might also play a role.…”
Section: Discussionmentioning
confidence: 92%
“…PCBs are known to have estrogenic, anti-estrogenic and antiandrogenic activities (Bonefeld-Jorgensen et al, 2001); p,p'-DDE was reported to have antiandrogenic properties (Kelce et al, 1995); HCB was reported to affect oestradiol levels in animals (Alvarez et al, 2000;Foster et al, 1995) and to interact with hormone receptors (Li et al, 2008); cadmium was observed to be able to interact with both oestrogen and androgen receptors (Stoica et al, 2000;Martin et al, 2002); lead was reported to have xenoestrogenic activity (Martin et al, 2003) and to affect pubertal development in girls (Selevan et al, 2003); polycyclic aromatic hydrocarbons were reported to affect development (Choi et al, 2006) and display as well AhR as estrogen receptor-mediated activity (Hilscherova et al, 2000). We wanted to test the hypothesis that low differences in levels of internal exposure (such as these occurring in the general population in Flanders) to endocrine disrupting substances result in differences in body size parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Den Hond et al (submitted) found a positive association between blood lead levels and the presence of gynecomastia (p ¼ 0.018). That higher blood lead levels might contribute to the risk of gynecomastia is perhaps not surprising as lead can have some xenoestrogenic properties (Martin et al, 2003).…”
Section: Article In Pressmentioning
confidence: 99%
“…The pollutants that were studied are known to have endocrine-disrupting properties. PCBs were reported to have estrogenic, anti-estrogenic and anti-androgenic activities (Bonefeld-Jorgensen et al, 2001;Hansen, 1998); p,p 0 -DDE is known to have anti-androgenic properties (Kelce et al, 1995); hexachlorobenzene (HCB) was reported to affect oestradiol levels in animals (Alvarez et al, 2000;Foster et al, 1995); cadmium was observed to be able to interact with both estrogen and androgen receptors (Martin et al, 2002;Stoica et al, 2000); lead was reported to have xeno-estrogenic activities (Martin et al, 2003) and to affect pubertal development in girls (Selevan et al, 2003;Wu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…According to some authors the bivalent metal cations Cd belongs to a new class of potent environmental estrogens, referred to as metalloestrogens. The studies in vivo and in vitro show that Cd acts like an estradiol activating estrogen receptor α through a high-affinity interaction with the hormone binding domain of the receptor [14,15]. There is evidence that the effects of cadmium are mediated by the estrogen receptor independent of estradiol [8].…”
Section: Introductionmentioning
confidence: 99%